Resurgence of malaria after discontinuation of indoor residual spraying of insecticide in a previously high transmission intensity area of Uganda - Raouf, Saned; Mpimbaza, Arthur; Kigozi, Ruth; Sserwanga, Asadu; Rubahika, Denis; Katamba, Henry; Lindsay, Steve W.; Kapella, Bryan K.; Belay, Kassahun A.; Kamya, Moses R.; Staedke, Sarah G.; Dorsey, Grant (The Lancet Global Health, 2016)
Indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) are the primary tools for malaria prevention in Africa. It is not known whether reductions in malaria can be sustained after IRS is discontinued. Our aim in this study was to assess changes in malaria morbidity in an area of Uganda with historically high transmission where IRS was discontinued after a 4-year period followed by universal LLIN distribution. Methods. Individual-level malaria surveillance data were collected from 1 outpatient department and 1 inpatient setting in Apac District, Uganda, from July 2009 through November 2015. Rounds of IRS were delivered approximately every 6 months from February 2010 through May 2014 followed by universal LLIN distribution in June 2014. Temporal changes in the malaria test positivity rate (TPR) were estimated during and after IRS using interrupted time series analyses, controlling for age, rainfall, and autocorrelation. Results. Data include 65 421 outpatient visits and 13 955 pediatric inpatient admissions for which a diagnostic test for malaria was performed. In outpatients aged <5 years, baseline TPR was 60%–80% followed by a rapid and then sustained decrease to 15%– 30%. During the 4–18 months following discontinuation of IRS, absolute TPR values increased by an average of 3.29% per month (95% confidence interval, 2.01%–4.57%), returning to baseline levels. Similar trends were seen in outpatients aged ≥5 years and pediatric admissions. Conclusions. Discontinuation of IRS in an area with historically high transmission intensity was associated with a rapid increase in malaria morbidity to pre-IRS levels.
Keywords: IRS; Malaria; Resurgence; LLIN; Uganda